2018
DOI: 10.1002/aoc.4399
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)‐N‐Heterocyclic Carbene Complexes: Efficient Catalysts for the Direct C‐H Bond Arylation of Furans with Aryl Halides

Abstract: This paper contains the synthesis and characterization of the seven new benzimidazolium salts and their corresponding new palladium(II)‐NHC complexes with the general formula [PdX2(NHC)2], (NHC = N‐heterocyclic carbene, X = Cl or Br), and also their catalytic activity in direct C‐H bond arylation of 2‐substituted furan derivatives with aryl bromides and aryl chlorides. Under the optimal conditions, these palladium(II)‐NHC complexes showed the good catalytic performance for the direct C‐H bond arylation of 2‐su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…In the presence of 2 mol% of 2f as the catalyst at 150 °C for 8 h, the C2-arylated benzothiazole derivative namely, 2-(4-acetylphenyl)-benzothiazole was obtained in full conversion with 86% isolated yield (Table 2, entry 2). When catalyst loading was decreased from 2 mol% to 1 mol% at 150 °C for 8 h, similar yield of product was also observed ( [56,57,[60][61][62] NMR data showed that all palladium(II)-NHC complexes were cis/trans mixtures. .…”
Section: Direct Arylation Of Benzoxazole and Benzothiazole With Aryl mentioning
confidence: 68%
See 3 more Smart Citations
“…In the presence of 2 mol% of 2f as the catalyst at 150 °C for 8 h, the C2-arylated benzothiazole derivative namely, 2-(4-acetylphenyl)-benzothiazole was obtained in full conversion with 86% isolated yield (Table 2, entry 2). When catalyst loading was decreased from 2 mol% to 1 mol% at 150 °C for 8 h, similar yield of product was also observed ( [56,57,[60][61][62] NMR data showed that all palladium(II)-NHC complexes were cis/trans mixtures. .…”
Section: Direct Arylation Of Benzoxazole and Benzothiazole With Aryl mentioning
confidence: 68%
“…[45][46][47][48] In this connection, recently, we have synthesized, characterized, and investigated palladium(II)-N-heterocyclic carbene (Pd-NHC) complexes for catalytic activity in the direct C-H bond activation of different (hetero)aromatic compounds with aryl halides. [49][50][51][52][53][54][55][56][57] The strong σ-donating but poor π-accepting ability of NHC ligands lead to the formation of many stable palladium(II)-NHC complexes. Due to activity, stability and selectivity of palladium(II)-NHC complexes, they have been widely used as highly reactive and rather selective catalysts for numerous direct arylation reactions.…”
Section: Scheme 1 Synthesis Of 2-arylsubstituted Benzoxazoles and Benmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it is known that cis and trans isomeric products form depending on the experimental conditions. [29][30][31] Recently, unusually, Han et al, performed a synthesis of a new type of bis(NHC)Pd(II) complexes from 1,3disubstituted NHC precursor containing bulky substituents in DMSO. 32 This complex contains both the NHC (carbene) ligand and the N-bound (NHC precursor) ligand.…”
Section: Introductionmentioning
confidence: 99%